A Church Without Bishops: Governance of the English Catholic Mission, 1594–1685. (2nd May 2017) - Schofield, Nicholas
Abstract : The Catholic community in early modern England was not only a persecuted minority but full of factions, each playing off the other, expressing themselves in a war of words, and even, on occasion, canvassing for support in the very establishment that was trying to eliminate them. To a large extent, these tensions were focused around the vexed question of what sort of ecclesiastical government should fill the vacuum left by the Reformation and the extinction of the Marian hierarchy. Various canonical solutions were tried: rule by archpriest, vicar apostolic and chapter of secular clergy. Each of these resulted in ongoing disagreements between secular and regular clergy, between those who viewed the English Catholic community as being in continuity with the pre-Reformation Church and those who thought circumstances required something new and creative. Added to this was a complex web of canonical jurisdictions, often without clear definition, and Rome's reluctance to act decisively and offend the Elizabethan or Stuart regime. This article, originally delivered as the Lyndwood Lecture, outlines the key personalities and events and examines the central issues that were at stake in this 'church without bishops'.